Reducing traffic violations in the online food delivery industry—A case study in Xi'an City, China - Lu, Xin-wei; Guo, Xiao-lu; Zhang, Jing-xiao; Li, Xiao-bing; Li, Li; Jones, Steven (Frontiers in Public Health, 2022)
Traffic accidents are ranked as one of the main threats to human life and public health. This is especially the case for the online food delivery industry, which in recent years has become a booming sector in China. However, this has resulted in a high level of traffic violations by deliverymen as well as crashes and the corresponding negative impact on public health. To reduce traffic violations by deliverymen and resulting crashes, a hierarchical online food delivery framework is proposed, which is based on data from questionnaire surveys conducted in Xi’an City, China. The study includes analysis of the root causes correlated with traffic violations during online food delivery as part of an empirical study on the priority delivery fee by applying a conditional price sensitivity measurement (PSM) model. The feasibility and rationality of the framework are further investigated by using cross analysis of urban dwellers’ occupation, income and commuting cost. The results identify that, through rationally shunting the demand of online food delivery, prolonging the default delivery duration, and providing diversified delivery services, the proposed hierarchical online food delivery mechanism is able to relieve the stress of deliverymen during peak hours of food requests. This reduces the willingness of deliverymen to engage in traffic violations, and other risky behaviors during food delivery trips. All of which facilitate high-quality and timely online food delivery service while enabling improved safety of deliverymen and others as part of enhanced public health.